2000
DOI: 10.1253/jcj.64.474
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Diverticulum Associated With Severe Mitral Regurgitation

Abstract: Diverticulum of the atrium is a rare and controversial clinical entity, and in the present case a left atrial diverticulum was associated with severe mitral regurgitation (MR). A 68-year-old female with the diagnosis of MR was referred for further cardiac evaluation. Echocardiography revealed severe MR and an accessory cavity behind an enlarged left atrium. She underwent surgical valve replacement, but excision of the diverticulum was not done because its rupture seemed unlikely. A follow-up computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 6 publications
1
37
0
1
Order By: Relevance
“…A more recent study by Abbara et al actually identified accessory diverticulae as having linear structures suggesting pectinate fibers at their orifice [15]. Atrial diverticulae, but not atrial aneurysms, are thought to contain myocardial sleeves, and thus, should demonstrate contraction during the cardiac cycle [4]. Such changes have been found in pulmonary vein ostia during atrial contraction, which demonstrate significant changes on size detected with cardiac CT or MRI [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study by Abbara et al actually identified accessory diverticulae as having linear structures suggesting pectinate fibers at their orifice [15]. Atrial diverticulae, but not atrial aneurysms, are thought to contain myocardial sleeves, and thus, should demonstrate contraction during the cardiac cycle [4]. Such changes have been found in pulmonary vein ostia during atrial contraction, which demonstrate significant changes on size detected with cardiac CT or MRI [16].…”
Section: Discussionmentioning
confidence: 99%
“…Other sites have also been shown to give rise to complex fragmented atrial electrograms (CFAE), including the interatrial septum, left atrial appendage and left atrium roof [3]. Small accessory appendages arising from the left atrial wall have also been identified with cardiac CT, which have been referred to variably as aneurysms or diverticulae [4,5]. Pathologically, a diverticulum contains normal myocardial wall structure and contracts in synchrony with the rest of the atrium, whereas aneurysms do not contain myocytes and therefore do not exhibit contractile properties [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal anatomy of the left atrial appendage has also been well studied [13]. During the routine clinical performance of coronary CT angiograms using a 64 slice ECG-gated CT scanner we have occasionally observed additional variations in the anatomy of the left atrium which are unusual and have been reported before as case reports or in small studies, such as atrial diverticuli [14][15][16][17][18], atrial aneurysms [19][20][21] and small accessory veins or fistulas originating from the left atrium which might look like diverticuli [12]. In this study we present an observational study of left atrial accessory appendages, and we report on the frequency and appearance of these lesser known anatomical variations of the left atrium in patients presenting for a clinical coronary CT angiogram using a 64 slice CT scanner.…”
Section: Introductionmentioning
confidence: 93%
“…Differential diagnosis of the accessory cavity includes cor triatriatum, left atrial aneurysm, diverticulum, and pulmonary varix. [5][6][7] A prominent confluence of the left atrial appendage and left pulmonary vein is easily distinguished from the partitioning membrane of the cor triatriatum by TEE. 8 Echocardiography demonstrated a connection between the cavity and the peripheral pulmonary veins, suggesting that in this case it was not a left atrial aneurysm.…”
Section: Discussionmentioning
confidence: 99%